HUMOROUS DISCOURSE ON THE MIDDLE EAST: ATTITUDE TOWARDS REPRESENTATION - Fauzan Novaldy; Dinda Noor Azizah (English Journal Literacy Utama, 2023)
Western perspective dominantly sees the Middle East in negative stereotypes. Many ways from many backgrounds start to criticize this perspective, including comedians utilizing comedy narration. This research aims at discovering how comedian represents Middle East and how the response manifests commenter’s attitude, applying descriptive qualitative research as a logical consequence that the data are in forms of stand-up performance transcription uploaded to YouTube and its sample comments from its comment column. Process of identifying Middle East representation and commenter’s attitude respectively utilizes Halliday’s transitivity and Martin & White’s appraisal system narrowed to attitude subsystem. The research results conclusions as follow. First, in terms of representation, the comedy narration provides an alternative platform to positively represent the Middle East, while second, commenter’s responses in attitude perspective mostly support the positive representation by showing their positive affection within themselves, favorable judgment in entity perspective, and affirmative appreciation to the happening event. This research attempt to see stimulated attitude after a representation in a specific social issue appears, while other researches documented in this writing integrate both theories at the same hierarchy. The relation varies in perspective of the audience stimulated by the discourse and who affirmatively experienced the discourse. At this point, comedy may have potency as a platform to pleasantly criticize sensitive issues